Proceedings of International Conference on Tourism Development: Building The Future Of Tourism - HBP, School of Housing Building & Planing (Sustainable Tourism Research Cluster, Universiti Sains Malaysia, 2013)
The International Conference on Tourism Development 2013 with the theme ‘Building the Future of Tourism’ is a sequal of the same event held on the 9-11th January 2005. The previous conference carried the theme ‘Tourism: Vehicle for Development’ triggered another angle of tourism research in this year’s affair. The conference organiser plans to make this academic activity an annual occasion since it was well received by participants. The proceeding compiles papers that are presented at this year’s conference. All presented papers went through strict peer-review before final papers are selected. It is hoped that the proceedings present high quality papers and worthy of discussions in line with the conference’s theme. This year’s event is organised by the Sustainable Tourism Research Cluster in collaboration with the Responsible Rural Tourism Network.